(3ehGQO GdhUhd Edi Yde GdCUhds - (3GdMSjfj, GdMdj, GdfLaj, GdbRhjfj, eMeO egOj Hf GdMSf, J (B1300(3g`s ((3YHO GdgGOj Hf YHO Ydj Bd GdTjN NVQs)
(3ChdgG (B:s
(3MeOG def CUd CUhd GdEjLGO(B... (3hHYO(B... (3Efg bO GdJeSfj CYR GdChdGO(B... (3Cf CDda aj GdCUhd GdabgjIs
(3BNQgG (B:s
(3EPG JYGOd GdOdjdGf (B... (3Ch GdQLhY Edi GdCUd hbjd HGdNjQ hbjd HGdhba hGdJNjjQ gfG ef HGH GdJhSYI(B... (3gPG BNQ eG CQOfG EjQGOg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B114s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs